Investigating the large angle of a physical pendulum using a smartphone's sensors. (28th May 2021) - Chatchawaltheerat, Theerawat; Khemmani, Supitch; Puttharugsa, Chokchai
Abstract: This paper demonstrates the use of a smartphone's sensors in recording experimental data for investigating the large angle of a physical pendulum. The smartphone (iPhone 5s) was attached to a beam to record simultaneously both the angular position and the angular speed of the beam oscillating about the pivot. The period and phase space of the oscillation were theoretically calculated and were compared with the experimental data. It was found that the experimental results agreed well with the theoretical calculations. We expect that this experiment based on a smartphone's sensors could be useful for physics teachers and encourage the interest of students.